Correlation of clinical profile with neuro imaging in patients with stroke - Sheikh, Arif S; Kulkarni, A.R. (International Journal of Health and Clinical Research, 2020)
Introduction: The cerebrovascular stroke is one of the leading causes of morbidity & mortality in adult life. After coronary heart disease & cancer of all types, stroke is the third commonest cause of death worldwide. Indian studies have shown a stroke prevalence of 471.58/100000 population. Objective: Primary objectives of the study were to study clinical profile, risk factors and to correlate clinical profile with neuroimaging in patients with stroke. Secondary objectives were to study the incidence of stroke in various socio-economic strata, the complications during the stay in hospital and also to determine the average length of hospital stay. Methods: This prospective hospital-based study was done of 50 consecutive patients with provisional clinical diagnosis of fresh stroke who underwent neuroimaging (CT/MRI) of brain. Patients with possible cause other than stroke were excluded from study. Imaging findings were evaluated and tabulated and subsequently correlated with the clinical findings of the patients. Results: There were 50 patients with stroke (32 males and 18 females). The study showed that cerebrovascular strokes are more common in males (64%) than females (36%), most common age group was 70-80 years (38%), most common clinical feature was hemiplegia (70%), most common risk factor was Hypertension (34%) followed by diabetes mellitus (38%), alcohol (20%), tobacco chewer (20%), smoking (18%), past h/o IHD (14%), past h/o cerebrovascular stroke (10%) dyslipidemia (4%). Most common type of stroke was ischemic (88%) and hemorrhagic was (12%). In ischemic stroke, most common involved areas were parietal (28%), frontal (28%). In hemorrhagic stroke most common site was thalamus (6%), basal ganglia (6%) followed by lentiform nucleus (4%). Provisional clinical diagnosis of infarct/ischemic stroke was given in 38 cases, and of hemorrhagic stroke in 12 cases out of total 50 cases. On neuroimaging infarcts/ ischemic stroke were diagnosed in 44 cases and hemorrhage in 6 cases. Clinical diagnosis in cases of ischemic stroke had Sensitivity of 84.1% and Specificity of 83.3%. While in cases of hemorrhagic stroke, the clinical diagnosis had Sensitivity of 83.3%, Specificity of 84.1%. Most commonly involved blood vessel was MCA territory (78%). The maximum number of days in hospital with either type of stroke was 6-10 days on an average. Most common associated complication was urinary tract infection 18.37 %(N=9) followed respiratory tract infection 6.12 %(N=3). Outcome of stroke patients, majority were discharged with variable residual disability while 4.5% (N=2) died during the hospital stay. Conclusion: In our study of 50 patients, hypertension was the most common risk factor and most common type of stroke was ischemic. Clinical diagnosis of stroke was accurate in a significant number of cases. In-hospital medical complications (vascular, urinary, and infectious) are relevant factors influencing duration of hospitalization after acute stroke. Therefore, prevention of potentially modifiable risk factors for medical complications is an important aspect of the early management of patients with stroke. Keywords: clinical profile,Neuroimaging,Computed Tomography, Magnetic Resonance Imaging.